2022
DOI: 10.1097/md.0000000000029820
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of esmolol in adults with sepsis and septic shock: An updated meta-analysis of randomized controlled trials

Abstract: Background: Sepsis affects millions of patients annually, resulting in substantial health and economic burdens globally. The role of esmolol potentially plays in the treatment of sepsis and septic shock in adult patients remains controversial.Methods: We undertook a systematic search of PubMed, EMBASE, and Cochrane Central Register of Controlled Trials databases from their inception to May 12, 2022, for randomized controlled trials that evaluated the efficacy of esmolol for sepsis and septic shock. A random-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
(136 reference statements)
1
17
0
Order By: Relevance
“…Similarly, there was no notable distinction in the vasopressor requirements between the beta-blocker and control groups. In agreement with our findings, previous meta-analyses investigated beta-blockers, either esmolol or landiolol benefit in a patient with septic shock or sepsis found a significant reduction in the 28 days mortality and heart rate in the beta-blocker group compared to the control group ( Li et al, 2020 , Zhang et al, 2022 ), with no significant effect on the length of ICU stay ( Hasegawa et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, there was no notable distinction in the vasopressor requirements between the beta-blocker and control groups. In agreement with our findings, previous meta-analyses investigated beta-blockers, either esmolol or landiolol benefit in a patient with septic shock or sepsis found a significant reduction in the 28 days mortality and heart rate in the beta-blocker group compared to the control group ( Li et al, 2020 , Zhang et al, 2022 ), with no significant effect on the length of ICU stay ( Hasegawa et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Morelli et al reported the safety of a short-acting β-blocker, esmolol, in patients with septic shock and noted a markedly reduced adjusted hazard ratio (HR) mortality of 61% but as a nonprimary outcome and with a high mortality in the control group of more than 80%. A recent meta-analysis of 8 randomized studies using esmolol suggested that the 32% risk ratio decreased 28-day mortality, and a meta-analysis of 7 studies using either esmolol or landiolol in patients with sepsis and septic shock was associated with 32% lower 28-day mortality. Landiolol (Rapibloc, AOP Health) is a very short-acting β-blocker and is approximately 8 times more selective for the β 1 -receptor than esmolol .…”
Section: Introductionmentioning
confidence: 99%
“…Third, it may be related to the role of β-blockers in regulating inflammatory response. β-blockers can down-regulate inflammatory mediators (e.g., TNF-α, IL-6, HMGB-1) in animal models of sepsis to reduce the inflammatory response ( 13 , 18 , 19 ) as well as inhibit cardiomyocyte apoptosis ( 20 , 21 ). In addition, β-blockers can activate the anti-inflammatory effects of cholecystokinin receptors and thus play a role in protecting the function of the intestinal barrier ( 18 ).…”
Section: Discussionmentioning
confidence: 99%